(untitled) (Experimental biology, 2015)
Rice Hull Ash (RHA) was converted to amorphous silica gel using a modified version of published literature procedures. The gels were characterized by a comparison of their CPMAS 29Si NMR and Scanning Electron Microscopy (SEM) images with commercial silica gels. The resulting gels were silanized with a 7.5:1 mixture of methyltrichlorosilane and chloropropyltrichlorosilane and then reacted with poly(allylamine) (PAA) to produce the silica polyamine composite (SPC) BP-1. The BP-1 was then further modified with pyridine-2-carboxaldehyde to form the copper selective SPC, CuSELECT. This procedure follows that used to produce the commercialized version of these composite materials from commercially available amorphous silica gels. The composites were characterized by solid state NMR techniques, elemental analysis, SEM, porosimetry, and metal ion capacity and selectivity. The overall goal of the project was to determine the feasibility of using RHA to make SPC. The observed strengths and weaknesses of this approach are discussed